2015
DOI: 10.3389/fmicb.2015.01197
|View full text |Cite
|
Sign up to set email alerts
|

The controversial nature of the Weissella genus: technological and functional aspects versus whole genome analysis-based pathogenic potential for their application in food and health

Abstract: Despite the use of several Weissella (W.) strains for biotechnological and probiotic purposes, certain species of this genus were found to act as opportunistic pathogens, while strains of W. ceti were recognized to be pathogenic for farmed rainbow trout. Herein, we investigated the pathogenic potential of weissellas based on in silico analyses of the 13 whole genome sequences available to date in the NCBI database. Our screening allowed us to find several virulence determinants such as collagen adhesins, aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 87 publications
5
87
1
1
Order By: Relevance
“…suggest their ability to adapt to different environment and different sugars availability (Abriouel et al, 2015). However, to the best of the authors' knowledge, there are no specific literature data on W. minor ability to ferment milk, but at the same time, some data are available about the inability W. confusa and Weissella cibaria to use lactose and galactose (Quattrini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggest their ability to adapt to different environment and different sugars availability (Abriouel et al, 2015). However, to the best of the authors' knowledge, there are no specific literature data on W. minor ability to ferment milk, but at the same time, some data are available about the inability W. confusa and Weissella cibaria to use lactose and galactose (Quattrini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several Weissella species are being extensively studied for their ability to produce significant amounts of extracellular polysaccharides (EPS), which can be used as prebiotics or in food industries with different technological applications (Abriouel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…W. ceti is considered to be a pathogen which infects fish and rainbow trout [193,194]. Genome sequence analysis of W. ceti strains revealed the presence of several virulence factors and antibiotic resistance genes [195], which comforts its potential pathogenicity. To the best of our knowledge, no study reported infections associated W. ceti in humans.…”
Section: Infections Associated With Weissellamentioning
confidence: 99%
“…With this regard, they can be considered as safe LAB. However, Abriouel et al (2015) showed the presence of genes coding for two aggregation substances ( Asa1/PrgB ) in W. oryzae SG25.…”
Section: Discussionmentioning
confidence: 99%